Bacteriophages : Part A - obocka, Magorzata; Szybalski, Wacaw T. (Advances in virus research, 2012)
This volume, the first of a two-part series, covers topics including historical, ecological and evolutionary considerations, genomics and molecular biology, and interaction of phages with their hosts.